2009
DOI: 10.1007/s00535-008-2275-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of nonsteroidal anti-inflammatory drug-induced gastropathy

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used for their analgesic, antipyretic, and antiinflammatory properties, and aspirin is increasingly employed in the primary and secondary prevention of cardiovascular disease and ischemic stroke. Despite undisputed therapeutic efficacy for these indications, all NSAIDs impart a considerable risk of peptic ulcer disease and upper gastrointestinal hemorrhage. A growing body of evidence supports an association between non-aspirin NSAIDs and acute coronary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 70 publications
0
28
0
1
Order By: Relevance
“…Consequently, many efforts were made for discovering selective cox-2 inhibitors. The first COX-2 selective inhibitor, Celecoxib (Celebrex), approved by the FDA in 1998 based upon the results of five clinical trials involving more than 5000 patients with degenerative or rheumatoid arthritis, showed comparable analgesia and efficacy to nonselective NSAIDs and placebo with fewer clinical and endoscopic gastrodudenal ulcers [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, many efforts were made for discovering selective cox-2 inhibitors. The first COX-2 selective inhibitor, Celecoxib (Celebrex), approved by the FDA in 1998 based upon the results of five clinical trials involving more than 5000 patients with degenerative or rheumatoid arthritis, showed comparable analgesia and efficacy to nonselective NSAIDs and placebo with fewer clinical and endoscopic gastrodudenal ulcers [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recommended that patients at low risk for gastrodudenal complications and without cardiovascular risk (i.e., not taking aspirin) are good candidates for NSAID monotherapy, whereas patients at high risk for GI events without cardiovascular risk require addition of misoprostol or a proton pump inhibitor, or discontinuation of NSAIDs and initiation of either a non-NSAID analgesic or a COX-2 inhibitor as monotherapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Given the clear involvement of TXA 2 /TPR signaling in the pathogenesis of multiple disease processes (eg, thrombosis and asthma) [10][11][12]39] , the limitations of aspirin therapy [15,16] , and evidence that antagonists are superior to aspirin in certain disease states [40] , there is an increasing interest in the development of TPR antagonists. Of note, due to a host of reasons, the use of antagonists developed (which were not rationally designed) [18][19][20][21]41] .…”
Section: Discussionmentioning
confidence: 99%
“…Based on these considerations, therapeutic strategies have focused on either modulating the synthesis of TXA 2 [13,14] , or interfering with its receptor binding. While, the former has been successfully targeted by the platelet COX-1 inhibitor aspirin, this therapeutic agent is associated with undesirable adverse effects (such as gastric ulcers) [15,16] , and resistance [17] . Regarding TPR antagonists; while many were developed [18][19][20][21] , none of them is currently available for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Недостатком этого препарата, как и других НПВП, являются выраженные побочные эффекты, особенно ульцерогенное (вызывающее язву) действие. Однако, высокая терапевтическая эффективность индометацина стимулирует разработки его новых лекарственных форм, направленных на снижение риска и тяжести побочных эффектов [1][2][3].…”
unclassified